Aluminum-magnesium spinel composite material, sagger, preparation method and application

By using aluminum-magnesium spinel composite material, the stability and erosion problems of existing shells when used at high temperatures are solved, and the production cost and longer service life are achieved, which is suitable for efficient production of melted nanocrystalline glass.

CN119707475APending Publication Date: 2025-03-28HUNAN JINGCI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311261078.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When used at high temperatures, existing scaffold materials have problems such as poor volume stability, insufficient chemical erosion capacity, high production cost and short service life. Especially in the process of melting nanocrystalline glass, problems such as unevenness, thermal erosion and color stains are difficult to avoid.

Method used

A cassette made of aluminum-magnesium spinel composite material, which is mixed with aluminum-magnesium spinel, electromelite, yttrium-stabilized magnesium zirconium aluminate, borate mineralizer and binder in a specific proportion and prepared by water spray agglomeration granulation and sintering process.

Benefits of technology

The aluminum-magnesium spinel silt has good chemical stability, corrosion resistance, thermal shock stability and low production costs. It can effectively prevent uneven and thermal erosion of nanocrystalline glass at high temperatures, extend the service life and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004478935370000151
    Figure BDA0004478935370000151
  • Figure BDA0004478935370000161
    Figure BDA0004478935370000161
  • Figure BDA0004478935370000291
    Figure BDA0004478935370000291
Patent Text Reader

Abstract

The invention discloses an aluminum-magnesium spinel composite material which is prepared by sintering the following raw material components in percentage by mass: 55-70% of aluminum-magnesium spinel; 10%-20% of electric smelting periclase; 5.2%-10.5% of yttrium oxide stabilized magnesium zirconate aluminate; 3%-10% of a borate mineralizing agent; and 0.5%-5% of a binding agent. The invention further discloses an aluminum-magnesium spinel sagger made of the aluminum-magnesium spinel composite material, a preparation method of the aluminum-magnesium spinel sagger and application of the aluminum-magnesium spinel sagger. The aluminum-magnesium spinel and the sagger have the advantages of good chemical stability, strong erosion resistance, abrasion resistance, good thermal shock resistance and the like, the preparation method is used for preparing the aluminum-magnesium spinel sagger, has the advantages of simple process steps, easily available raw materials, low cost and the like, and can be applied to melting of nano glass ceramics, so that the sagger has good application prospects. The problems of cracks, deformation, thermal erosion and the like of the nanocrystalline glass can be avoided, and the production cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional refractory materials, and in particular relates to an aluminum-magnesium spinel composite material, a sagger, a preparation method and an application thereof. Background Art

[0002] A sagger is a protective auxiliary material container used to hold the load of ceramic products (such as nano-glass-ceramics) during the firing process. It is made of refractory materials.

[0003] At present, the refractory materials used to make saggers are mainly silicon, clay, high alumina, and corundum, among which high-purity mullite and corundum (including hollow alumina balls) lightweight refractory products have the best performance. However, in practical applications, there are still many unsatisfactory aspects. For example, mullite thermal insulation refractory materials have low operating temperature, large high-temperature shrinkage, poor volume stability, weak resistance to chemical erosion, and high production costs, while corundum refractory materials have large volume density and thermal conductivity, poor erosion resistance, extremely high production costs, and short life when used in places with large temperature fluctuations.

[0004] Nano-glass crystals are a high-grade glass-ceramic material. Their production process is generally carried out by melting in a glass melting furnace. However, their melting temperature is as high as 1600-1800°C, and they are difficult to clarify. They take a long time to melt, consume a lot of energy, and have high requirements for refractory materials. Currently, glass melting furnaces all use platinum-rhodium-zirconium-rhenium alloy as the liner to protect the molten glass from being contaminated by refractory materials. The investment cost is huge, and the service life is short (generally no more than one year). 2 tons / day to 3 tons / day will cost more than 1 billion yuan, and the production cost is high. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an aluminum-magnesium spinel composite material, a sagger, a preparation method and an application thereof in view of the above-mentioned deficiencies in the prior art. The aluminum-magnesium spinel composite material and the sagger have the advantages of good chemical stability (acid and alkali resistance), strong corrosion resistance, not easy to be damaged, good thermal shock stability, etc. The preparation method is used to prepare the above-mentioned aluminum-magnesium spinel sagger, and has the advantages of simple process steps, easy availability of raw materials, low cost, high production efficiency, etc. The aluminum-magnesium spinel sagger is used for melting nano-microcrystalline glass, opening up a new way to melt nano-microcrystalline glass with a sagger, which can avoid the problems of inhomogeneous phase in nano-microcrystalline glass, the inability of the sagger to resist heat erosion, color pollution, dispersion, severe birefringence, etc., effectively reducing production costs, improving the rate of genuine products, and being suitable for commercial mass production.

[0006] The technical solution of the present invention to solve the above technical problems is:

[0007] According to a first aspect of the present invention, there is provided an aluminum-magnesium spinel composite material, which is sintered by raw material components including the following mass percentages:

[0008] Aluminum-magnesium spinel 55% to 70%;

[0009] Fused periclase 10% to 20%;

[0010] Yttria stabilized magnesium zirconate aluminate 5.2% to 10.5%;

[0011] Borate mineralizer 3% to 10%;

[0012] Binder 0.5%~5%.

[0013] Preferably, the aluminum-magnesium spinel is made of raw materials comprising the following mass percentages: aluminum oxide 72%; magnesium oxide 28%.

[0014] Preferably, the yttria-stabilized magnesium zirconate aluminate comprises magnesium zirconate aluminate and yttria, wherein the magnesium zirconate aluminate is made of raw materials comprising the following mass percentages: 46.4% zirconium oxide; 38.5% aluminum oxide; 15.1% magnesium oxide; and the amount of yttria is 0.2% to 0.5% of the mass of the magnesium zirconate aluminate.

[0015] Preferably, the borate mineralizer is a divalent metal salt borate mineralizer, specifically one of a calcium borate mineralizer, a zinc borate mineralizer, a magnesium borate mineralizer, and a barium borate mineralizer.

[0016] Preferably, the calcium borate mineralizer is made of raw materials comprising the following mass percentages: 39% calcium oxide and 61% boron oxide.

[0017] Preferably, the aluminum-magnesium spinel composite material comprises the following components in mass percentage:

[0018] MgO: 31.19%~40.79%;

[0019] Al2O3: 45.56% ~ 54.44%;

[0020] ZrO2: 2.42%~5.13%;

[0021] B2O3: 1.84%~6.42%;

[0022] CaO: 1.18%~4.11%;

[0023] Y2O3: 0.01%~0.05%.

[0024] Preferably, the zinc borate mineralizer is made of raw materials comprising the following mass percentages: 60% zinc oxide and 40% boron oxide.

[0025] Preferably, the aluminum-magnesium spinel composite material comprises the following components in mass percentage:

[0026] MgO: 31.19%~40.79%;

[0027] Al2O3: 45.56%~54.44%;

[0028] ZrO2: 2.42%~5.13%;

[0029] B2O3: 1.21%~4.21%;

[0030] ZnO: 1.81%~6.32%;

[0031] Y2O3: 0.01%~0.05%.

[0032] Preferably, the magnesium borate mineralizer is made of raw materials including the following mass percentages: 46.6% magnesium oxide and 53.4% ​​boron oxide.

[0033] Preferably, the aluminum-magnesium spinel composite material comprises the following components in mass percentage:

[0034] MgO: 35.03%~45.73%;

[0035] Al2O3: 45.74% ~ 57.31%;

[0036] ZrO2: 2.42%~5.13%;

[0037] B2O3: 1.62%~5.62%;

[0038] Y2O3: 0.01%~0.05%.

[0039] Preferably, the barium borate mineralizer is made of raw materials including the following mass percentages: 64% barium carbonate and 36% boron oxide.

[0040] Preferably, the aluminum-magnesium spinel composite material comprises the following components in mass percentage:

[0041] MgO: 31.19%~40.79%;

[0042] Al2O3: 45.56%~54.44%;

[0043] ZrO2: 2.42%~5.13%;

[0044] B2O3: 1.09%~3.79%;

[0045] BaO: 1.51%~5.23%;

[0046] Y2O3: 0.01%~0.05%.

[0047] Preferably, the particle sizes of the alumina-magnesia spinel, the fused periclase, the yttria-stabilized magnesium aluminozirconate, and the borate mineralizer are 120-200 meshes.

[0048] According to a second aspect of the present invention, there is provided an aluminum-magnesium-spinel sagger, which is made of the aluminum-magnesium-spinel composite material described above.

[0049] According to a third aspect of the present invention, there is provided a method for preparing an aluminum-magnesium spinel sagger, comprising:

[0050] The aluminum-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, borate mineralizer, and binder are uniformly mixed according to the mass percentage in the aluminum-magnesium spinel composite material according to any one of claims 1 to 13 to obtain a mixture;

[0051] The mixed material is subjected to water spray agglomeration and granulation to obtain a sagger material;

[0052] The sagger material is pressed into shape, sintered and cooled to obtain an alumina-magnesia spinel sagger.

[0053] Preferably, the particle size of the sagger material is 0.5-3 mm.

[0054] Preferably, the sintering process includes:

[0055] First, heat to 500°C at a heating rate of 2°C / min;

[0056] Then continue heating to 1400°C at a heating rate of 10°C to 12°C / min;

[0057] Then continue heating to 1600°C at a heating rate of 8°C to 10°C / min;

[0058] Finally, sintering is carried out at 1600°C for 30 to 60 minutes.

[0059] Preferably, the cooling process comprises:

[0060] First, cool to 1200°C at a cooling rate of 8-10°C / min;

[0061] Then continue cooling to 500°C at a cooling rate of 6-8°C / min;

[0062] Finally, continue cooling to room temperature at a cooling rate of 2°C to 3°C / min.

[0063] According to a fourth aspect of the present invention, there is provided an application of the above-mentioned alumina-magnesium spinel sagger, which is applied to melting nano-ceramic glass.

[0064] Preferably, the nano-ceramic glass is melted by mixing various raw materials for making nano-ceramic glass in a proportion and then putting them into an alumina-magnesium spinel sagger, and then putting the alumina-magnesium spinel sagger containing the batch materials for melting the nano-ceramic glass into a high-temperature kiln, so that the batch materials for melting the nano-ceramic glass are melted and clarified at the glass melting temperature;

[0065] Then, the clarified glass liquid in the sagger is cooled to the crystallization temperature of the nano-microcrystalline glass by controlling the temperature of the kiln, so as to obtain a nano-microcrystalline glass ingot integrated with the sagger;

[0066] The nano-crystalline glass ingot is cut and processed, the sagger and the nano-crystalline glass ingot are directly cut together, the sagger shell is removed to obtain the nano-crystalline glass ingot, and then the nano-crystalline glass ingot is processed into the required nano-crystalline glass products, such as cutting the nano-crystalline glass ingot into slices to make nano-crystalline glass products such as mobile phone panels or PDA panels and back panels.

[0067] Beneficial effects:

[0068] The aluminum-magnesium-spinel composite material and the functional sagger of the sagger of the present invention have the advantages of good chemical stability (acid and alkali resistance), strong resistance to erosion by molten glass, not easy to break, high load softening point (no softening at 1700°C), good thermal shock stability, etc. The preparation method of the present invention is used to prepare the above-mentioned composite material aluminum-magnesium-spinel functional sagger, and has the advantages of simple process steps, easy availability of raw materials, low cost, high production efficiency, etc. It is used to melt high-transparency, high-mechanical strength nano-microcrystalline glass with a precise annealing optical path difference of less than 20nm / cm, which can avoid the problems of cracks, phase separation, coarsening, devitrification, color pollution, etc. in the nano-microcrystalline glass, and can smoothly carry out commercial large-scale production, effectively reducing production costs. DETAILED DESCRIPTION

[0069] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0070] Example 1

[0071] This embodiment discloses an aluminum-magnesium spinel composite material, which has aluminum-magnesium spinel as a main crystal phase and is sintered by raw material components including the following mass percentages:

[0072] Aluminum-magnesium spinel 55% to 70%;

[0073] Fused periclase 10% to 20%;

[0074] Yttria stabilized magnesium zirconate aluminate 5.2% to 10.5%;

[0075] Borate mineralizer 3% to 10%;

[0076] Binder 0.5%~5%.

[0077] In some embodiments, the aluminum-magnesium spinel is made of raw materials including the following mass percentages: aluminum oxide 72%; magnesium oxide 28%.

[0078] Specifically, the inventors have found in experiments that the obvious feature of the spinel family of minerals is that it is a solid spinel in which metal ion components can be replaced. One or two metal ions in the components can be replaced in large quantities by other metal ion components in this group of minerals, and the replacement is done without changing the crystal structure or deforming the lattice. Both magnesium ions and aluminum ions can be replaced by other ions of smaller sizes to maintain electrochemical equilibrium. Therefore, the spinel family of minerals has many kinds of solid solutions, but no natural resources of these spinels as raw materials for refractory materials have been found, and they must be prepared by synthesis.

[0079] The component content range of aluminum-magnesium spinel is wide, and its performance varies greatly. After a large number of experiments, the inventors found that within the component range of aluminum oxide and magnesium oxide in this embodiment (i.e., 72% aluminum oxide and 28% magnesium oxide), the obtained aluminum-magnesium spinel has better chemical stability (acid and alkali resistance), higher volume density, and resistance to alkali metal and alkaline earth metal ion corrosion at high temperatures. As the raw material of the composite material of this embodiment, it can improve the chemical stability (acid and alkali resistance), corrosion resistance, thermal shock stability and other properties.

[0080] In this embodiment, the synthesis process of aluminum magnesium spinel is as follows:

[0081] Raw materials of aluminum oxide and magnesium oxide with a fineness of 500 to 1000 mesh are taken in proportion, mixed evenly, and then heated to 1600° C. at a heating rate of 5 to 6° C. / min, and kept warm for 30 minutes, and then the aluminum-magnesium spinel can be sintered.

[0082] In this embodiment, the fused periclase is commercially available fused periclase with a fineness of 120-200 meshes.

[0083] In some embodiments, yttria-stabilized magnesium zirconate aluminate includes magnesium zirconate aluminate and yttria, wherein the magnesium zirconate aluminate is made of raw materials including the following mass percentages: 46.4% zirconium oxide; 38.5% aluminum oxide; 15.1% magnesium oxide; and the amount of yttria is 0.2% to 0.5% of the mass of the magnesium zirconate aluminate. Yttria can be used as a stabilizer for zirconium oxide to prevent the crystal transformation of zirconium oxide during the cooling process, and can also promote the growth and development of the crystal structure of zirconium aluminum magnesium garnet. In addition, it can also play a role in resisting alkali metal ion corrosion, further improving the corrosion resistance.

[0084] In this embodiment, the synthesis process of yttria-stabilized magnesium zirconate aluminate is as follows:

[0085] Raw materials of zirconium oxide, aluminum oxide, magnesium oxide and stabilizer yttrium oxide with a fineness of 500 to 1000 mesh are taken in proportion, mixed evenly, and then heated to 1400 to 1450° C. at a heating rate of 6 to 8° C. / min, and kept warm for 30 minutes to sinter the yttrium oxide-stabilized magnesium zirconate aluminate.

[0086] In some embodiments, the borate mineralizer is a borate mineralizer of a divalent metal salt, preferably one of a calcium borate mineralizer, a zinc borate mineralizer, a magnesium borate mineralizer, and a barium borate mineralizer, which promotes the formation of a low eutectic point glassy liquid phase during the high-temperature sintering process, which can reduce the sintering temperature during the generation of the aluminum-magnesium spinel composite material, so that the aluminum-magnesium spinel composite material can grow and develop crystals at a relatively low temperature, thereby reducing the thermal engineering cost of the synthesis of the aluminum-magnesium spinel composite material. At the same time, it can also increase the thermal shock stability of the aluminum-magnesium spinel composite material, and make it into a sagger, which can increase the number of reuses of the sagger and extend its service life.

[0087] Specifically, the calcium borate mineralizer is made of raw materials including the following mass percentages: calcium oxide (CaO) 39%, boron oxide (B2O3) 61%. The synthesis process of the calcium borate mineralizer is as follows:

[0088] Raw materials of calcium oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5-6° C. / min, kept warm for a period of time (such as 30 minutes), and then sintered to obtain the calcium borate mineralizer.

[0089] When the calcium borate mineralizer is used, the aluminum-magnesium spinel composite material includes the following components in mass percentage:

[0090] MgO: 31.19%~40.79%;

[0091] Al2O3: 45.56%~54.44%;

[0092] ZrO2: 2.42%~5.13%;

[0093] B2O3: 1.84%~6.42%;

[0094] CaO: 1.18%~4.11%;

[0095] Y2O3: 0.01%~0.05%.

[0096] Specifically, the barium borate mineralizer is made of raw materials including the following mass percentages: 64% barium carbonate and 36% boron oxide. The synthesis process of the barium borate mineralizer is as follows:

[0097] Take raw materials of barium carbonate and boron oxide with a fineness of about 300 meshes in proportion, mix them evenly, and then heat them to 900° C. at a heating rate of 5-6° C. / min, and keep them warm for a period of time (such as 30 minutes) to sinter the barium borate mineralizer.

[0098] When the above-mentioned barium borate mineralizer is used, the aluminum-magnesium spinel composite material includes the following components in mass percentage:

[0099] MgO: 31.19%~40.79%;

[0100] Al2O3: 45.56%~54.44%;

[0101] ZrO2: 2.42%~5.13%;

[0102] B2O3: 1.09%~3.79%;

[0103] BaO: 1.51%~5.23%;

[0104] Y2O3: 0.01%~0.05%.

[0105] Specifically, the zinc borate mineralizer is made of raw materials including the following mass percentages: 60% zinc oxide and 40% boron oxide. The synthesis process of the zinc borate mineralizer is as follows:

[0106] Raw materials of zinc oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5-6° C. / min, and kept warm for a period of time (such as 30 minutes) to sinter the zinc borate mineralizer.

[0107] When the above zinc borate mineralizer is used, the aluminum-magnesium spinel composite material includes the following components in mass percentage:

[0108] MgO: 31.19%~40.79%;

[0109] Al2O3: 45.56%~54.44%;

[0110] ZrO2: 2.42%~5.13%;

[0111] B2O3: 1.21%~4.21%;

[0112] ZnO: 1.81%~6.32%;

[0113] Y2O3: 0.01%~0.05%.

[0114] Specifically, the magnesium borate mineralizer is made of raw materials including the following mass percentages: 46.6% magnesium oxide and 53.4% ​​boron oxide. The synthesis process of the magnesium borate mineralizer is as follows:

[0115] Raw materials of magnesium oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5-6° C. / min, and kept warm for a period of time (such as 30 minutes) to sinter the magnesium borate mineralizer.

[0116] When the above-mentioned magnesium borate mineralizer is used, the aluminum-magnesium spinel composite material includes the following components in mass percentage:

[0117] MgO: 35.03%~45.73%;

[0118] Al2O3: 45.74%~57.31;

[0119] ZrO2: 2.42%~5.13%;

[0120] B2O3: 1.62%~5.62%;

[0121] Y2O3: 0.01%~0.05%.

[0122] In some embodiments, the particle size of aluminum-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, and borate mineralizer is 120-200 mesh. The particle size is too large and the specific surface area is small, making it difficult to fully contact with other raw materials. The physical and chemical properties of the obtained aluminum-magnesium spinel composite material are poor, which affects the strength of the aluminum-magnesium spinel composite material.

[0123] The aluminum-magnesium spinel composite material of this embodiment has the advantages of good chemical stability (acid and alkali resistance), strong resistance to erosion by molten glass, not easy to be damaged, high load softening point (no softening at 1700°C), and good thermal shock stability.

[0124] Example 2

[0125] This embodiment discloses an aluminum-magnesium spinel sagger, which is made of the aluminum-magnesium spinel composite material described in Example 1 and is a composite material sagger with an expansion coefficient very close to that of the glass phase, high strength, high load softening point, and high chemical stability.

[0126] Specifically, the performance parameters of the sagger in this embodiment are as follows:

[0127] Density of 2.9 tons / cubic meter and above;

[0128] Apparent porosity ≤ 0.48%;

[0129] Compressive strength>1240Mpa;

[0130] The linear expansion coefficient is (20℃-800℃)11×10 -6 / ℃ and below;

[0131] The softening start temperature under load of 0.2 MPa is above 1700°C.

[0132] It should be noted that the shape and size of the sagger in this embodiment can be adjusted according to actual needs. In some embodiments, the sagger in this embodiment is preferably a rectangular sagger without a cover, and the size of the sagger is preferably:

[0133] a. The inner wall of the sagger (length × width × height) is 280mm × 200mm × 90mm, and the thickness is 12mm;

[0134] b. The inner wall of the sagger (length × width × height) is 290mm × 290mm × 1000mm, and the thickness is 14mm;

[0135] c. The inner wall of the sagger (length × width × height) is 430mm × 430mm × 130mm, and the thickness is 14mm.

[0136] Example 3

[0137] This embodiment discloses an application of the aluminum-magnesium spinel sagger described in Example 2, which can be widely used in the fields of molten metals, alkali metal molten salts, chemical laboratories, electrochemical material processes, glass manufacturing, etc., especially in the in-situ melting of nano-microcrystalline glass, and has a very broad application prospect.

[0138] Specifically, in the process of melting nano-glass-ceramics by the in-situ method, the sagger needs to be filled with glass precursor materials at 1400℃~1600℃, and the multi-layer saggers need to be stacked and placed in a ceramic firing kiln at 1400℃~1600℃ for melting-clarification-homogenization-cooling, and then crystallized at 800℃~700℃ and annealed at 600℃~500℃. Therefore, the in-situ method of melting nano-glass-ceramics requires the high temperature resistance of the sagger to be very stable, and needs to meet the following requirements:

[0139] ① Load softening point: >1700℃, to prevent high temperature kiln collapse accidents;

[0140] ②Linear expansion coefficient range: (20℃-800℃)12×10 -6 / ℃ and below;

[0141] ③ There is only an intermediate layer of 0.1-0.4 mm between the sagger phase and the glass phase (a coating applied before melting the nano-ceramic glass is an interface isolation protective layer separating the sagger and the glass, so that they maintain their own independent and specific physical and chemical properties);

[0142] ④ Thermal behavior of the sagger: no microcracks occur to prevent accidents of glass liquid outflow;

[0143] ⑤ The glass in the sagger has no sagger particles or component diffusion;

[0144] ⑥ The porosity of the sagger sintering opening is less than 0.5%, and the compressive strength is greater than 1200Mpa;

[0145] ⑦ Density is 2.7 tons / cubic meter and above.

[0146] By comparing the performance parameters of the sagger of the present embodiment, the density, apparent porosity, compressive strength and linear expansion coefficient of the sagger of the present embodiment can fully meet the requirements of melting nano-microcrystalline glass for saggers, and has the advantages of good chemical stability (acid and alkali resistance), strong corrosion resistance, not easy to be corroded, good thermal shock stability, etc., and because its linear expansion coefficient is similar to that of nano-microcrystalline glass, it can avoid the problems of cracks, deformation, thermal erosion and the like in the nano-microcrystalline glass. In addition, after the melting of the nano-microcrystalline glass is completed, when the sagger of the present embodiment is cut and separated from the nano-microcrystalline glass at room temperature, no stress cracking will occur, resulting in any dimensional damage to the glass, and the sagger waste after cutting can also be used as a raw material for sagger production, thereby effectively reducing the production cost.

[0147] Specifically, the melting of the nano-ceramic glass is to mix various raw materials for making the nano-ceramic glass in a proportion and evenly put them into an alumina-magnesium spinel sagger, and then put the alumina-magnesium spinel sagger containing the nano-ceramic glass mixture into a high-temperature kiln, so that the nano-ceramic glass mixture is melted and clarified at the glass melting temperature, wherein the heating rate is controlled to be 6-8°C / min in the range of room temperature to 1000°C, the heating rate is controlled to be 8-10°C / min in the range of 1000°C to 1400°C, and the heating rate is controlled to be 2-5°C / min in the range of 1400°C to 1500°C. The temperature is kept at 1500℃ for 2 hours, and the heating rate is controlled to be 2-5℃ / min in the range of 1500℃-1600℃, and the temperature is kept at 1600℃ for 2 hours; then the clarified glass liquid in the sagger is cooled to the crystallization temperature of the nano-microcrystalline glass by controlling the temperature of the kiln to obtain a nano-microcrystalline glass ingot; the nano-microcrystalline glass ingot is cut and processed, and the sagger shell is removed to obtain a nano-microcrystalline glass ingot, and then the nano-microcrystalline glass ingot is processed into the required nano-microcrystalline glass product, such as cutting the nano-microcrystalline glass ingot into pieces to make products such as mobile phone panels or handheld computer panels and back panels. The waste cut off after removing the sagger shell can be recycled as sagger raw materials or glass raw materials. The nano-microcrystalline glass produced by this in-situ production method has high quality, few impurities, few bubbles, high strength, high hardness, high transparency, and a precision annealing optical path difference of less than 20nm / cm.

[0148] Example 4

[0149] This embodiment discloses a method for preparing an aluminum-magnesium spinel sagger, which is used to prepare the aluminum-magnesium spinel sagger described in Example 1, and comprises the following steps:

[0150] S1, mixing aluminum magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate aluminate, borate mineralizer, and the aluminum magnesium spinel composite material according to Example 1 by mass percentage (i.e., aluminum magnesium spinel 55% to 70%; fused periclase 10% to 20%; yttria-stabilized magnesium zirconate aluminate 5.2% to 10.5%; borate mineralizer 3% to 10%; binder 0.5% to 5%) to obtain a mixture;

[0151] S2, agglomerating and granulating the mixed material by water spraying to obtain a sagger material;

[0152] S3, pressing the sagger material into shape, and obtaining the alumina-magnesia spinel sagger after sintering and cooling.

[0153] Compared with the prior art, the aluminum-magnesium spinel sagger made by the method of this embodiment has the advantages of good chemical stability (acid and alkali resistance), strong corrosion resistance, not easy to be damaged, good thermal shock stability, easy sintering, low cost, etc. It can be widely used in molten metals, alkali metal molten salts, chemical laboratories, electrochemical material processes, glass manufacturing and other fields, especially in the in-situ melting of nano-microcrystalline glass, and has a very broad application prospect.

[0154] In some embodiments, the aluminum-magnesium spinel is made of raw materials including the following mass percentages: aluminum oxide 72%; magnesium oxide 68%.

[0155] The synthesis process of aluminum-magnesium spinel is as follows: take raw materials aluminum oxide and magnesium oxide with a fineness of 500-1000 mesh in proportion, mix them evenly, heat them to 1600°C at a heating rate of 5-6°C / min, and keep them warm for 30 minutes to sinter the aluminum-magnesium spinel.

[0156] In this embodiment, the fused periclase is commercially available fused periclase with a fineness of 120-200 meshes.

[0157] In some embodiments, yttria-stabilized magnesium zirconate aluminate includes magnesium zirconate aluminate and added yttria, wherein the magnesium zirconate aluminate is made of raw materials including the following mass percentages: 46.4% zirconium oxide; 38.5% aluminum oxide; 15.1% magnesium oxide; and the amount of yttria is 0.2% to 0.5% of the mass of the magnesium zirconate aluminate.

[0158] The synthesis process of yttria-stabilized magnesium zirconate aluminate is as follows: raw materials of zirconium oxide, aluminum oxide, magnesium oxide and stabilizer yttria with a fineness of 500 to 1000 mesh are taken in proportion, mixed evenly, and then heated to 1400 to 1450° C. at a heating rate of 6 to 8° C. / min, and kept warm for 30 minutes to sinter the yttria-stabilized magnesium zirconate aluminate.

[0159] In some embodiments, the borate mineralizer is a borate mineralizer of a divalent metal salt, preferably one of a calcium borate mineralizer, a zinc borate mineralizer, a magnesium borate mineralizer, and a barium borate mineralizer, which promotes the formation of a low eutectic point glassy liquid phase during high-temperature sintering, which can reduce the sintering temperature during the generation of the aluminum-magnesium spinel composite material, so that the aluminum-magnesium spinel composite material can grow and develop crystals at a relatively low temperature, thereby reducing the thermal engineering cost of the synthesis of the aluminum-magnesium spinel composite material. At the same time, it can also increase the thermal shock stability of the aluminum-magnesium spinel composite material, and make it into a sagger, which can increase the number of reuses of the sagger and extend its service life.

[0160] In some more specific embodiments, the calcium borate mineralizer is made of raw materials comprising the following mass percentages: 39% calcium oxide and 61% boron oxide.

[0161] The synthesis process of the calcium borate mineralizer is as follows: raw materials calcium oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5 to 6° C. / min, and kept warm for a period of time (such as 30 minutes) to sinter the calcium borate mineralizer.

[0162] In some more specific embodiments, the barium borate mineralizer is made of raw materials including the following mass percentages: 64% barium carbonate and 36% boron oxide.

[0163] The synthesis process of the barium borate mineralizer is as follows: take raw materials of barium carbonate and boron oxide with a fineness of about 300 mesh in proportion, mix them evenly, and then heat them to 900° C. at a heating rate of 5 to 6° C. / min, keep them warm for a period of time (such as 30 minutes), and then sinter the barium borate mineralizer.

[0164] In some more specific embodiments, the zinc borate mineralizer is made of raw materials comprising the following mass percentages: 60% zinc oxide and 40% boron oxide.

[0165] The synthesis process of the zinc borate mineralizer is as follows: raw materials of zinc oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5 to 6° C. / min, and kept warm for a period of time (such as 30 minutes) to calcine the zinc borate mineralizer.

[0166] In some more specific embodiments, the magnesium borate mineralizer is made of raw materials including the following mass percentages: 46.6% magnesium oxide and 53.4% ​​boron oxide.

[0167] The synthesis process of the magnesium borate mineralizer is as follows: raw materials of magnesium oxide and boron oxide with a fineness of about 300 mesh are taken in proportion, mixed evenly, and then heated to 900° C. at a heating rate of 5 to 6° C. / min, and kept warm for a period of time (such as 30 minutes) to sinter the magnesium borate mineralizer.

[0168] In some embodiments, the particle sizes of the alumina-magnesia spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and borate mineralizer in step S1 are 120-200 meshes. The binder is preferably CMC (sodium carboxymethyl cellulose).

[0169] In some embodiments, the particle size of the sagger material obtained by water spray agglomeration granulation is 0.5-3 mm, wherein preferably 2-3 mm particle size accounts for 60%, 1-2 mm particle size accounts for 30%, and 0.5-1 mm particle size accounts for 10%, which is more conducive to compression molding.

[0170] In some embodiments, the sagger material is pressed into shape in step S3 by dry pressing, and the mechanical pressure is >5000 tons.

[0171] In some embodiments, the sintering process uses programmed temperature increase, and the specific process includes:

[0172] First, heat to 500°C at a heating rate of 2°C / min;

[0173] Then continue heating to 1400°C at a heating rate of 10°C to 12°C / min;

[0174] Then continue heating to 1600°C at a heating rate of 8°C to 10°C / min;

[0175] Finally, sintering is carried out at 1600°C for 30 to 60 minutes.

[0176] The above-mentioned sintering temperature fully considers each raw material component and its performance. Since the preparation method of this embodiment adds borate mineralizers such as calcium borate that are in a glassy state under high temperature conditions, the sintering temperature of aluminum-magnesium spinel during its generation can be reduced, so that the aluminum-magnesium spinel composite material can grow and develop its crystal form at a lower temperature than the traditional aluminum-magnesium spinel sintering temperature (above 1800°C). When the sintering temperature is 1600°C, aluminum-magnesium spinel can be better generated, thereby making the performance of the sagger more stable. If the calcination temperature is too low, the sagger cannot be sintered. If the calcination temperature is too high, it is easy to produce overburning and other phenomena, causing cracks in the sagger and reducing the strength of the sagger. The calcination time and calcination temperature cooperate with each other to achieve the best sintering effect.

[0177] In some embodiments, the cooling process adopts programmed cooling to avoid cracks caused by too fast cooling. The specific process includes:

[0178] First, cool down to 1200°C at a cooling rate of 8-10°C / min, such as cooling down to 1200°C at a cooling rate of 8-10°C / min from the highest temperature of 1600°C during sintering;

[0179] Then continue cooling to 500°C at a cooling rate of 6-8°C / min;

[0180] Finally, continue cooling to room temperature at a cooling rate of 2°C to 3°C / min.

[0181] Several groups of specific preparation examples and comparative examples are provided below to further describe the aluminum-magnesium spinel sagger and the preparation method thereof in the present invention in detail, as follows:

[0182] Preparation Example 1

[0183] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0184] Aluminum magnesium spinel: 55%;

[0185] Fused periclase: 20%;

[0186] Yttria-stabilized magnesium zirconate aluminate: 10.5%;

[0187] Calcium borate mineralizer: 10%;

[0188] Binder CMC: 4.5%.

[0189] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide accounts for 61% by mass of calcium oxide in calcium borate mineralizer, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0190] Table 1 Raw material components of preparation examples 1-20 aluminum magnesium spinel sagger (mass percentage)

[0191]

[0192]

[0193] Preparation Example 2

[0194] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0195] Magnesium aluminate spinel: 58.5%;

[0196] Fused periclase: 19%;

[0197] Yttria-stabilized magnesium zirconate aluminate: 9.5%;

[0198] Calcium borate mineralizer: 8%;

[0199] Binder CMC: 5%.

[0200] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide accounts for 61% by mass of calcium oxide in calcium borate mineralizer, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0201] Preparation Example 3

[0202] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0203] Magnesium aluminum spinel: 63%;

[0204] Fused periclase: 18%;

[0205] Yttria-stabilized magnesium zirconate aluminate: 7.5%;

[0206] Calcium borate mineralizer: 8%;

[0207] Binder CMC: 3.5%.

[0208] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide accounts for 61% by mass of calcium oxide in calcium borate mineralizer, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0209] Preparation Example 4

[0210] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0211] Magnesium aluminum spinel: 66%;

[0212] Fused periclase: 15%;

[0213] Yttria-stabilized magnesium zirconate aluminate: 8.3%;

[0214] Calcium borate mineralizer: 8.7%;

[0215] Binder CMC: 2%.

[0216] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.2% by mass of magnesium aluminozirconate; boron oxide in calcium borate mineralizer accounts for 61% by mass, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0217] Preparation Example 5

[0218] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0219] Magnesium aluminum spinel: 70%;

[0220] Fused periclase: 14%;

[0221] Yttria-stabilized magnesium zirconate aluminate: 6.3%;

[0222] Calcium borate mineralizer: 7.7%;

[0223] Binder CMC: 2%.

[0224] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.2% by mass of magnesium aluminozirconate; boron oxide in calcium borate mineralizer accounts for 61% by mass, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0225] Preparation Example 6

[0226] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0227] Magnesium aluminum spinel: 55%;

[0228] Fused periclase: 20%;

[0229] Yttria-stabilized magnesium zirconate aluminate: 10.5%;

[0230] Zinc borate mineralizer: 10%;

[0231] Binder CMC: 4.5%.

[0232] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in zinc borate mineralizer accounts for 40% by mass, and zinc oxide accounts for 60% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and zinc borate mineralizer is 150 mesh.

[0233] Preparation Example 7

[0234] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0235] Magnesium aluminate spinel: 58.5%;

[0236] Fused periclase: 19%;

[0237] Yttria-stabilized magnesium zirconate aluminate: 9.5%;

[0238] Zinc borate mineralizer: 8%;

[0239] Binder CMC: 5%.

[0240] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in zinc borate mineralizer accounts for 40% by mass, and zinc oxide accounts for 60% by mass. The particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and zinc borate mineralizer is 150 mesh.

[0241] Preparation Example 8

[0242] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0243] Magnesium aluminum spinel: 63%;

[0244] Fused periclase: 18%;

[0245] Yttria-stabilized magnesium zirconate aluminate: 7.5%;

[0246] Zinc borate mineralizer: 8%;

[0247] Binder CMC: 3.5%.

[0248] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass, aluminum oxide accounts for 38.5% by mass, magnesium oxide accounts for 15.1% by mass, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in zinc borate mineralizer accounts for 40% by mass, and zinc oxide accounts for 60% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and zinc borate mineralizer is 150 mesh.

[0249] Preparation Example 9

[0250] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0251] Magnesium aluminum spinel: 66%;

[0252] Fused periclase: 15%;

[0253] Yttria-stabilized magnesium zirconate aluminate: 8.3%;

[0254] Zinc borate mineralizer: 8.7%;

[0255] Organic binder CMC: 2%.

[0256] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria accounts for 0.2% by mass of magnesium alumino-zirconate; boron oxide in zinc borate mineralizer accounts for 40% by mass, and zinc oxide accounts for 60% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and zinc borate mineralizer is 150 mesh.

[0257] Preparation Example 10

[0258] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0259] Magnesium aluminum spinel: 70%;

[0260] Fused periclase: 14%;

[0261] Yttria-stabilized magnesium zirconate aluminate: 6.3%;

[0262] Zinc borate mineralizer: 7.7%;

[0263] Binder CMC: 2%.

[0264] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria accounts for 0.2% by mass of magnesium alumino-zirconate; boron oxide in zinc borate mineralizer accounts for 40% by mass, and zinc oxide accounts for 60% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and zinc borate mineralizer is 150 mesh.

[0265] Preparation Example 11

[0266] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0267] Magnesium aluminum spinel: 55%;

[0268] Fused periclase: 20%;

[0269] Yttria-stabilized magnesium zirconate aluminate: 10.5%;

[0270] Magnesium borate mineralizer: 10%;

[0271] Organic binder CMC: 4.5%.

[0272] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.2% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.3% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.0% by mass of magnesium alumino-zirconate, and yttria accounts for 0.5% by mass of magnesium alumino-zirconate; boron oxide in magnesium borate mineralizer accounts for 53.4% ​​by mass, and magnesium oxide accounts for 46.6% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and magnesium borate mineralizer is 150 mesh.

[0273] Preparation Example 12

[0274] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0275] Magnesium aluminate spinel: 58.5%;

[0276] Fused periclase: 19%;

[0277] Yttria-stabilized magnesium zirconate aluminate: 9.5%;

[0278] Magnesium borate mineralizer: 8%;

[0279] Binder CMC: 5%.

[0280] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria accounts for 0.5% by mass of magnesium alumino-zirconate; boron oxide in magnesium borate mineralizer accounts for 53.4% ​​by mass, and magnesium oxide accounts for 46.6% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and magnesium borate mineralizer is 150 mesh.

[0281] Preparation Example 13

[0282] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0283] Magnesium aluminum spinel: 63%;

[0284] Fused periclase: 18%;

[0285] Yttria-stabilized magnesium zirconate aluminate: 7.5%;

[0286] Magnesium borate mineralizer: 8%;

[0287] Binder CMC: 3.5%.

[0288] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria accounts for 0.5% by mass of magnesium alumino-zirconate; boron oxide in magnesium borate mineralizer accounts for 53.4% ​​by mass, and magnesium oxide accounts for 46.6% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and magnesium borate mineralizer is 150 mesh.

[0289] Preparation Example 14

[0290] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0291] Magnesium aluminum spinel: 66%;

[0292] Fused periclase: 15%;

[0293] Yttria-stabilized magnesium zirconate aluminate: 8.3%;

[0294] Magnesium borate mineralizer: 8.7%;

[0295] Organic binder CMC: 2%.

[0296] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria-stabilized magnesium alumino-zirconate accounts for 0.2% by mass; boron oxide in magnesium borate mineralizer accounts for 53.4% ​​by mass, and magnesium oxide accounts for 46.6% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and magnesium borate mineralizer is 150 mesh.

[0297] Preparation Example 15

[0298] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0299] Magnesium aluminum spinel: 70%;

[0300] Fused periclase: 14%;

[0301] Yttria-stabilized magnesium zirconate aluminate: 6.3%;

[0302] Magnesium borate mineralizer: 7.7%;

[0303] Binder CMC: 2%.

[0304] Among them, magnesium oxide in magnesium aluminum spinel accounts for 28% by mass, aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium alumino-zirconate accounts for 46.4% by mass of magnesium alumino-zirconate, aluminum oxide accounts for 38.5% by mass of magnesium alumino-zirconate, magnesium oxide accounts for 15.1% by mass of magnesium alumino-zirconate, and yttria accounts for 0.2% by mass of magnesium alumino-zirconate; boron oxide in magnesium borate mineralizer accounts for 53.4% ​​by mass, and magnesium oxide accounts for 46.6% by mass. The particle size of magnesium aluminum spinel, fused periclase, yttria-stabilized magnesium alumino-zirconate, and magnesium borate mineralizer is 150 mesh.

[0305] Preparation Example 16

[0306] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0307] Magnesium aluminum spinel: 55%;

[0308] Fused periclase: 20%;

[0309] Yttria-stabilized magnesium zirconate aluminate: 10.5%;

[0310] Barium borate mineralizer: 10%;

[0311] Binder CMC: 4.5%.

[0312] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in barium borate mineralizer accounts for 36% by mass, and barium carbonate accounts for 64% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and barium borate mineralizer is 150 mesh.

[0313] Preparation Example 17

[0314] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0315] Magnesium aluminate spinel: 58.5%;

[0316] Fused periclase: 19%;

[0317] Yttria-stabilized magnesium zirconate aluminate: 9.5%;

[0318] Barium borate mineralizer: 8%;

[0319] Binder CMC: 5%.

[0320] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in barium borate mineralizer accounts for 36% by mass, and barium carbonate accounts for 64% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and barium borate mineralizer is 150 mesh.

[0321] Preparation Example 18

[0322] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0323] Magnesium aluminum spinel: 63%;

[0324] Fused periclase: 18%;

[0325] Yttria-stabilized magnesium zirconate aluminate: 7.5%;

[0326] Barium borate mineralizer: 8%;

[0327] Binder CMC: 3.5%.

[0328] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.0% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide in barium borate mineralizer accounts for 36% by mass, and barium carbonate accounts for 64% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and barium borate mineralizer is 150 mesh.

[0329] Preparation Example 19

[0330] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0331] Magnesium aluminum spinel: 66%;

[0332] Fused periclase: 15%;

[0333] Yttria-stabilized magnesium zirconate aluminate: 8.3%;

[0334] Barium borate mineralizer: 8.7%;

[0335] Binder CMC: 2%.

[0336] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.2% by mass of magnesium aluminozirconate; boron oxide in barium borate mineralizer accounts for 36% by mass, and barium carbonate accounts for 64% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and barium borate mineralizer is 150 mesh.

[0337] Preparation Example 20

[0338] As shown in Table 1, an aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0339] Magnesium aluminum spinel: 70%;

[0340] Fused periclase: 14%;

[0341] Yttria-stabilized magnesium zirconate aluminate: 6.3%;

[0342] Barium borate mineralizer: 7.7%;

[0343] Binder CMC: 2%.

[0344] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.2% by mass of magnesium aluminozirconate; boron oxide in barium borate mineralizer accounts for 36% by mass, and barium carbonate accounts for 64% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and barium borate mineralizer is 150 mesh.

[0345] Preparation Example 21

[0346] A magnesium-aluminum spinel sagger, which is different from Example 1 in that the particle sizes of magnesium-aluminum spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer are 180 meshes.

[0347] The method for preparing the aluminum-magnesium spinel sagger in Preparation Examples 1 to 21 comprises the following steps:

[0348] S1, mixing alumina-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, borate mineralizer, and binder uniformly according to the mass percentage in the alumina-magnesium spinel sagger described in Preparation Example 1 to obtain a mixture;

[0349] S2, agglomerating and granulating the mixed material by water spraying to obtain a sagger material of 0.5-3 mm;

[0350] S3, pressing the sagger material into shape, and heating it to 500°C at a heating rate of 2°C / min, and then continuing to heat it to 1400°C at a heating rate of 11°C / min, and then continuing to heat it to 1600°C at a heating rate of 9°C / min, and finally sintering it at 1600°C for 45 minutes, and then cooling it to 1200°C at a cooling rate of 9°C / min, and then continuing to cool it to 500°C at a cooling rate of 7°C / min, and finally continuing to cool it to room temperature at a cooling rate of 2°C / min to obtain an aluminum-magnesium spinel sagger.

[0351] The following is an example of melting nano-ceramic glass using the aluminum-magnesium spinel obtained in Preparation Example 1. The specific process is as follows:

[0352] According to mass percentage, 14% of sodium oxide, 1.2% of lithium oxide, 20% of aluminum oxide, 60% of silicon dioxide, and 4.8% of 30 nanometer MgO·Al2O3 spinel are uniformly mixed to obtain a nano-ceramic glass mixture;

[0353] The nano-ceramic glass mixture is placed in the aluminum-magnesium spinel sagger prepared in Preparation Example 1, and then placed in a high-temperature kiln for sintering, wherein the heating rate is controlled to be 7°C / min in the range of room temperature to 1000°C, the heating rate is controlled to be 9°C / min in the range of 1000°C to 1400°C, the heating rate is controlled to be 3°C / min in the range of 1400°C to 1500°C, and the mixture is kept at 1500°C for 2 hours, and the heating rate is controlled to be 4°C / min in the range of 1500°C to 1600°C, and the mixture is kept at 1600°C for 2 hours, so that the nano-ceramic glass mixture is melted and clarified at the glass melting temperature;

[0354] Afterwards, the clarified glass liquid in the sagger was cooled to 700°C by controlling the furnace temperature and kept at that temperature for 1 hour, then cooled to 500°C at a cooling rate of 1°C / min and kept at that temperature for 3 hours, and then cooled to room temperature at a cooling rate of 1°C / min to obtain a nano-crystal glass ingot;

[0355] The nano-ceramic glass ingot is cut and processed, and the sagger shell is removed to obtain the nano-ceramic glass ingot, and then the nano-ceramic glass ingot is cut and processed into pieces according to the use of the nano-ceramic glass (for example, as a mobile phone panel) to make the final nano-ceramic glass product. After testing, the above-prepared nano-ceramic glass product has no impurities, no bubbles, bending strength ≥ 1200MPa, Mohs hardness reaches level 6, transparency is greater than 91%, and the precision annealing optical path difference is 19.4nm / cm. The cut sagger shell and other waste materials are recycled as sagger raw materials or glass raw materials.

[0356] Comparative Example 1

[0357] An aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0358] Magnesium aluminum spinel: 50%;

[0359] Fused periclase: 25%;

[0360] Yttria-stabilized magnesium zirconate aluminate: 10%;

[0361] Calcium borate mineralizer: 10%;

[0362] Binder CMC: 5%.

[0363] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% by mass, and aluminum oxide accounts for 72% by mass; zirconium oxide in yttria-stabilized magnesium aluminozirconate accounts for 46.4% by mass of magnesium aluminozirconate, aluminum oxide accounts for 38.5% by mass of magnesium aluminozirconate, magnesium oxide accounts for 15.1% by mass of magnesium aluminozirconate, and yttria accounts for 0.5% by mass of magnesium aluminozirconate; boron oxide accounts for 61% by mass of calcium oxide in calcium borate mineralizer, and calcium oxide accounts for 39% by mass; the particle size of magnesium aluminozirconate spinel, fused periclase, yttria-stabilized magnesium aluminozirconate, and calcium borate mineralizer is 150 mesh.

[0364] Different from Preparation Example 1, the amount of magnesia-alumina spinel and fused periclase raw materials used in Comparative Example 1 is not within the range provided by the present invention.

[0365] Comparative Example 2

[0366] An aluminum-magnesium spinel sagger is sintered by raw material components including the following mass percentages:

[0367] Magnesium aluminum spinel: 55%;

[0368] Fused periclase: 20%;

[0369] Yttria-stabilized magnesium zirconate aluminate: 10.5%;

[0370] Calcium borate mineralizer: 10%;

[0371] Organic binder CMC: 4.5%.

[0372] Among them, magnesium oxide in magnesium aluminate spinel accounts for 28% of the mass, and aluminum oxide accounts for 72% of the mass; zirconium oxide in yttria-stabilized magnesium zirconium aluminate accounts for 46.4% of the mass of magnesium zirconium aluminate, aluminum oxide accounts for 38.5% of the mass of magnesium zirconium aluminate, magnesium oxide accounts for 15.1% of the mass of magnesium zirconium aluminate, and yttrium oxide accounts for 0.5% of the mass of magnesium zirconium aluminate; boron oxide accounts for 61% of the mass of calcium oxide in calcium borate mineralizer, and calcium oxide accounts for 39% of the mass.

[0373] Different from Preparation Example 1, in Comparative Example 2, the aluminum magnesium spinel with a particle size of 150 mesh, fused periclase, yttria-stabilized magnesium zirconate, and calcium borate mineralizer are replaced with aluminum magnesium spinel with a particle size of 300 mesh, fused periclase, yttria-stabilized magnesium zirconate, and calcium borate mineralizer.

[0374] Comparative Example 3

[0375] A magnesium-aluminum spinel sagger, which is different from Preparation Example 1 in that the raw materials of Comparative Example 3 lack a calcium borate mineralizer.

[0376] Comparative Example 4

[0377] A magnesium-aluminum spinel sagger, which is different from Preparation Example 1 in that the raw materials of Comparative Example 4 lack yttria-stabilized magnesium aluminozirconate.

[0378] Comparative Example 5

[0379] A method for preparing an aluminum-magnesium spinel sagger comprises the following steps:

[0380] S1, mixing alumina-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, borate mineralizer, and binder uniformly according to the mass percentage in the alumina-magnesium spinel sagger described in Preparation Example 1 to obtain a mixture;

[0381] S2, agglomerating and granulating the mixed material by water spraying to obtain a sagger material of 0.5-3 mm;

[0382] S3, pressing the sagger material into shape, continuously heating to 1600°C at a heating rate of 10°C / min and keeping the temperature for 60min, then cooling to 1200°C at a cooling rate of 9°C / min, then cooling to 500°C at a cooling rate of 7°C / min, and finally cooling to room temperature at a cooling rate of 2°C / min to obtain an aluminum-magnesium spinel sagger.

[0383] The difference between this comparative example and Preparation Example 1 is that the sintering process of this comparative example does not adopt the programmed temperature rising process as described in Preparation Example 1.

[0384] Comparative Example 6

[0385] A method for preparing an aluminum-magnesium spinel sagger comprises the following steps:

[0386] S1, mixing alumina-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, borate mineralizer, and binder uniformly according to the mass percentage in the alumina-magnesium spinel sagger described in Preparation Example 1 to obtain a mixture;

[0387] S2, agglomerating and granulating the mixed material by water spraying to obtain a sagger material of 0.5-3 mm;

[0388] S3, pressing the sagger material into shape, and heating it to 500°C at a heating rate of 2°C / min, and then continuing to heat it to 1400°C at a heating rate of 11°C / min, and then continuing to heat it to 1600°C at a heating rate of 9°C / min, and finally sintering it at 1600°C for 45 minutes, and then naturally cooling it to room temperature to obtain an aluminum-magnesium spinel sagger.

[0389] The difference between this comparative example and Preparation Example 1 is that the cooling process of this comparative example does not adopt the programmed cooling process as described in Preparation Example 1.

[0390] Performance test ①: Under the same conditions, the physical properties of the saggers in Preparation Examples 1 to 21 and Comparative Examples 1 to 6, such as density, apparent porosity, compressive strength, linear expansion coefficient, and 0.2 MPa load softening starting temperature, were tested. The results are shown in Table 2.

[0391] Table 2 Physical properties test results

[0392]

[0393]

[0394] As shown in Table 2, the density of the saggers described in Preparation Examples 1 to 21 is 2.7 tons / m3 or above, the apparent porosity is below 0.5%, the compressive strength is >1200Mpa, and the linear expansion coefficient (20℃-800℃) is 12×10 -6 / ℃ and below, no softening at 1700℃ (i.e., the softening start temperature under 0.2Mpa load is above 1700℃), and all performance index parameters have reached the mechanical strength performance requirements of the in-situ melting nano-ceramic glass for the sagger. However, the above performance indicators of each sagger in Comparative Examples 1 to 6 have obvious defects compared with the mechanical strength performance requirements of the in-situ melting nano-ceramic glass for the sagger, and have not fully met the mechanical strength performance requirements of the in-situ melting nano-ceramic glass for the sagger.

[0395] Performance Test ②: The saggers in Preparation Examples 1 to 21 and Comparative Examples 1 to 6 were respectively used to carry out in-situ melting of nano-glass ceramics (comprising the following components in mass percentage: 14% sodium oxide; 1.2% lithium oxide; 20% aluminum oxide; 60% silicon dioxide; 4.8% 30 nanometer MgO·Al2O3 spinel) at 1550°C. The test results are shown in Table 3.

[0396] Table 3 Test results of nano-ceramic glass melted in situ at 1550℃

[0397]

[0398]

[0399] As shown in Table 3, the saggers described in Preparation Examples 1 to 21 are not deformed, cracked, and there are no sagger particles or component diffusion on the nano-ceramic glass. It can be seen that they can meet the requirements of the in-situ method for melting nano-ceramic glass on the performance of the sagger, proving that the aluminum-magnesium spinel sagger provided by the present invention has the advantages of good chemical stability (acid and alkali resistance), strong corrosion resistance, not easy to abrasion, and good thermal shock stability at a high temperature of 1550°C for melting nano-ceramic glass after the reasonable combination of various raw materials. However, the saggers described in Comparative Examples 1 to 6 all have problems such as deformation, cracks, and obvious sagger particles or component diffusion on the nano-ceramic glass. It can be seen that by changing the content of each raw material or deleting any of the raw materials or changing the sintering heating method or changing the cooling method after sintering or using the existing sagger, the chemical stability, corrosion resistance, abrasion resistance, thermal shock stability and other properties of the sagger will deteriorate, so that it is difficult to meet the requirements of the in-situ method for melting nano-ceramic glass on the performance of the sagger.

[0400] Performance Test ③: The saggers in Preparation Examples 1 to 21 and Comparative Examples 1 to 6 were respectively used to carry out in-situ melting of nano-glass ceramics (comprising the following components by mass percentage: 15% sodium carbonate + potassium carbonate; 10% calcium oxide; 29% aluminum oxide; 44% silicon dioxide) at 1600°C. The test results are shown in Table 4.

[0401] Table 4 Test results of nano-ceramic glass melted in situ at 1600℃

[0402]

[0403]

[0404] As shown in Table 4, the saggers described in Preparation Examples 1 to 21 are not deformed, cracked, and there are no sagger particles or component diffusion on the nano-ceramic glass. It can be seen that it can meet the requirements of the in-situ method for melting nano-ceramic glass on the performance of the sagger, and it can also prove that the aluminum-magnesium spinel sagger provided by the present invention has good chemical stability (acid and alkali resistance), strong corrosion resistance, not easy to abrasion, and good thermal shock stability at a high temperature of 1600°C for melting nano-ceramic glass after the reasonable combination of various raw materials. However, the saggers described in Comparative Examples 1 to 6 all have problems such as deformation, cracks, and obvious sagger particles or component diffusion on the nano-ceramic glass. It can be seen that by changing the content of each raw material or deleting any of the raw materials or changing the sintering heating method or changing the cooling method after sintering or using the existing sagger, the chemical stability, corrosion resistance, abrasion resistance, thermal shock stability and other properties of the sagger will deteriorate, so that it is difficult to meet the requirements of the in-situ method for melting nano-ceramic glass on the performance of the sagger.

[0405] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. An aluminum-magnesium spinel composite material, characterized in that: It is sintered by raw material components including the following mass percentages: Aluminum-magnesium spinel 55% to 70%; Fused periclase 10% to 20%; Yttria stabilized magnesium zirconate aluminate 5.2% to 10.5%; Borate mineralizer 3% to 10%; Binder 0.5%~5%.

2. The aluminum-magnesium spinel composite material according to claim 1, characterized in that: The aluminum-magnesium spinel is made of raw materials including the following mass percentages: 72% aluminum oxide and 28% magnesium oxide.

3. The aluminum-magnesium spinel composite material according to claim 1, characterized in that: The yttria-stabilized magnesium zirconate aluminate comprises magnesium zirconate aluminate and yttria, wherein the magnesium zirconate aluminate is made of raw materials comprising the following mass percentages: 46.4% zirconium oxide; 38.5% aluminum oxide; and 15.1% magnesium oxide. The amount of yttrium oxide is 0.2% to 0.5% of the mass of magnesium zirconate aluminate.

4. The aluminum-magnesium spinel composite material according to claim 1, characterized in that: The borate mineralizer is a borate mineralizer of a divalent metal salt, and specifically may be one of a calcium borate mineralizer, a zinc borate mineralizer, a magnesium borate mineralizer, and a barium borate mineralizer.

5. The aluminum-magnesium spinel composite material according to claim 4, characterized in that: The calcium borate mineralizer is made of raw materials including the following mass percentages: 39% calcium oxide and 61% boron oxide.

6. The aluminum-magnesium spinel composite material according to claim 5, characterized in that: The aluminum-magnesium spinel composite material comprises the following components in percentage by mass: MgO: 31.19%~40.79%; Al2O3: 45.56%~54.44%; ZrO2: 2.42%~5.13%; B2O3: 1.84%~6.42%; CaO: 1.18%~4.11%; Y2O3: 0.01%~0.05%.

7. The aluminum-magnesium spinel composite material according to claim 4, characterized in that: The zinc borate mineralizer is made of the following raw materials in percentage by mass: 60% zinc oxide and 40% boron oxide.

8. The aluminum-magnesium spinel composite material according to claim 7, characterized in that: The aluminum-magnesium spinel composite material comprises the following components in percentage by mass: MgO: 31.19%~40.79%; Al2O3: 45.56%~54.44%; ZrO2: 2.42%~5.13%; B2O3: 1.21%~4.21%; ZnO: 1.81%~6.32%; Y2O3: 0.01%~0.05%.

9. The aluminum-magnesium spinel composite material according to claim 4, characterized in that: The magnesium borate mineralizer is made of raw materials including the following mass percentages: 46.6% magnesium oxide and 53.4% ​​boron oxide.

10. The aluminum-magnesium spinel composite material according to claim 9, characterized in that: The aluminum-magnesium spinel composite material comprises the following components in percentage by mass: MgO: 35.03%~45.73%; Al2O3: 45.74% ~ 57.31%; ZrO2: 2.42%~5.13%; B2O3: 1.62%~5.62%; Y2O3: 0.01%~0.05%.

11. The aluminum-magnesium spinel composite material according to claim 4, characterized in that: The barium borate mineralizer is made of the following raw materials in percentage by mass: 64% barium carbonate and 36% boron oxide.

12. The aluminum-magnesium spinel composite material according to claim 11, characterized in that: The aluminum-magnesium spinel composite material includes the following components in percentage by mass: MgO: 31.19%~40.79%; Al2O3: 45.56%~54.44%; ZrO2: 2.42%~5.13%; B2O3: 1.09%~3.79%; BaO: 1.51%~5.23%; Y2O3: 0.01%~0.05%.

13. The aluminum-magnesium spinel composite material according to claim 1, characterized in that: The particle sizes of the alumina-magnesia spinel, the fused periclase, the yttria-stabilized magnesium aluminozirconate, and the borate mineralizer are 120-200 meshes.

14. An aluminum-magnesium spinel sagger, characterized in that: It is made of the aluminum-magnesium spinel composite material described in any one of claims 1 to 13.

15. A method for preparing an aluminum-magnesium spinel sagger, comprising: The aluminum-magnesium spinel, fused periclase, yttria-stabilized magnesium zirconate, borate mineralizer, and binder are uniformly mixed according to the mass percentage in the aluminum-magnesium spinel composite material according to any one of claims 1 to 13 to obtain a mixture; The mixed material is subjected to water spray agglomeration and granulation to obtain a sagger material; The sagger material is pressed into shape, sintered and cooled to obtain an alumina-magnesia spinel sagger.

16. The aluminum-magnesium spinel sagger according to claim 15, characterized in that: The particle size of the sagger material is 0.5-3 mm.

17. The aluminum-magnesium spinel sagger according to claim 15, characterized in that: The sintering process includes: First, heat to 500°C at a heating rate of 2°C / min; Then continue heating to 1400°C at a heating rate of 10°C to 12°C / min; Then continue heating to 1600°C at a heating rate of 8°C to 10°C / min; Finally, sintering is carried out at 1600°C for 30 to 60 minutes.

18. The aluminum-magnesium spinel sagger according to claim 15, characterized in that: The cooling process includes: First, cool to 1200°C at a cooling rate of 8-10°C / min; Then continue cooling to 500°C at a cooling rate of 6-8°C / min; Finally, continue cooling to room temperature at a cooling rate of 2°C to 3°C / min.

19. An application of the aluminum-magnesium spinel sagger according to claim 14, characterized in that: Used in melting nano-glass-ceramics.

20. The use of the aluminum-magnesium spinel sagger according to claim 19, characterized in that: The melting of nano-glass-ceramics is to mix various raw materials for making nano-glass-ceramics in a proportion and evenly put them into an alumina-magnesia-spinel sagger, and then put the alumina-magnesia-spinel sagger containing the batch materials for melting the nano-glass-ceramics into a high-temperature kiln, so that the batch materials for melting the nano-glass-ceramics are melted and clarified at the glass melting temperature; Then, the clarified glass liquid in the sagger is cooled to the crystallization temperature of the nano-microcrystalline glass by controlling the temperature of the kiln, so as to obtain a nano-microcrystalline glass ingot integrated with the sagger; The nano-microcrystalline glass ingot is cut and processed, the sagger and the nano-microcrystalline glass ingot are directly cut together, the sagger shell is removed to obtain the nano-microcrystalline glass ingot block, and then the nano-microcrystalline glass ingot block is processed into the required nano-microcrystalline glass product.